Extracellular vesicles in Graves’ disease and Graves’ orbitopathy: immunoregulatory mechanisms, biomarkers, and therapeutic potentials - Chen, Yuqing; Yang, Ying; Yang, Shuo; Yuan, Wenjie; Jiang, Lihong; Wei, Ruili (Frontiers in Immunology, 2026)
Graves’ disease (GD) is a common autoimmune thyroid disorder and is often accompanied by Graves’ orbitopathy (GO), an inflammatory eye disease that can significantly reduce the quality of patients’ life. Despite understanding of GD and GO has progressed, the mechanisms driving disease progression remain incompletely defined. Emerging evidence highlights extracellular vesicles (EVs), particularly exosomes, as important mediators of immune regulation and tissue remodeling in autoimmune disorders, including GD and GO. This review summarizes current knowledge of EVs biogenesis and molecular compositions, highlighting their contributions to GD and GO pathogenesis. We also discuss the diagnostic and prognostic potential of EV-associated miRNAs and proteins, and consider findings from other immune-mediated ocular diseases to place these observations in a broader immunopathological context. Overall, EVs appear to be actively involved in GD and GO and may serve as useful tools for disease monitoring and therapy development. Nonetheless, challenges such as methodological variability and limited functional validation remains. Standardized protocols and larger, multicenter studies are needed to support the clinical translation of EV-based approaches.